Dominant Lethal Effects of Cyfluthrin and Malathion on Mice - Pagulayan, Imelda; Villa, Leilani Margarita (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Male ICR strain mice were treated with three sublethal doses of malathion and cyfluthrin (Baythroid) through oral administration and intraperitoneal injection. One week after treatment, they were caged with two females and were allowed to mate. Seven days after the appearance of vaginal plugs, the females were dissected and observed for dominant lethality. Cyfluthrin came out as the more effective inducer of mutagenesis. The study found out that cyfluthrin was dose and route dependent but such results were not exhibited by malathion.